2009
DOI: 10.1021/jp807116q
|View full text |Cite
|
Sign up to set email alerts
|

Reductive Defluorination of Aqueous Perfluorinated Alkyl Surfactants: Effects of Ionic Headgroup and Chain Length

Abstract: Perfluorinated chemicals (PFCs) are distributed throughout the environment. In the case of perfluorinated alkyl carboxylates and sulfonates, they can be classified as persistent organic pollutants since they are resistant to environmentally relevant reduction, oxidation, and hydrolytic processes. With this in mind, we report on the reductive defluorination of perfluorobutanoate, PFBA (C(3)F(7)CO(2)(-)), perfluorohexanoate, PFHA (C(5)F(11)CO(2)(-)), perfluorooctanoate, PFOA (C(7)F(15)CO(2)(-)), perfluorobutane … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
240
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 263 publications
(260 citation statements)
references
References 47 publications
16
240
4
Order By: Relevance
“…1) is distinctly reflected on the first-order PFOA removal rate value and half-life period (Table 1). The PFOA removal rate for UVC20/KI in this investigation is about 2.6-fold larger than the value reported in Park et al (2009 and2010), but it is about twofold smaller than the value reported in Qu et al (2010). An optimum KI dosage and alkaline solution pH (&9.0) are shown to enhance reductive degradation of PFOA with UVC (Qu et al 2010).…”
Section: Resultscontrasting
confidence: 66%
See 2 more Smart Citations
“…1) is distinctly reflected on the first-order PFOA removal rate value and half-life period (Table 1). The PFOA removal rate for UVC20/KI in this investigation is about 2.6-fold larger than the value reported in Park et al (2009 and2010), but it is about twofold smaller than the value reported in Qu et al (2010). An optimum KI dosage and alkaline solution pH (&9.0) are shown to enhance reductive degradation of PFOA with UVC (Qu et al 2010).…”
Section: Resultscontrasting
confidence: 66%
“…UV photolysis of KI with 254-and 185-nm photons Although formation of aquated electrons due to KI photolysis with 254-and 185-nm photons was confirmed in the 1960s (Jortner et al 1964), their (i.e., e aq -) usefulness in reductive degradation of PFCs was recognized recently (Huang et al 2007;Park et al 2009;Park 2010;Qu et al 2010). Similar to those results, the UVC20/KI process was more efficient than UVC20 in terms of PFOA elimination and defluorination in this investigation.…”
Section: Defluorination Ratios and Ratesmentioning
confidence: 99%
See 1 more Smart Citation
“…21 However, the quantification of these reaction intermediates is challenging due to the lack of The presence of C x F 2x+1 I indicates that the sulfonate group is readily cleaved during irradiation. After 2.5 h of photolysis, 0.422 Âą 0.016 mg of C 8 F 17 I was produced (Fig.…”
Section: Uv-iodide Photolytic Pfc Reduction: Gaseous Products and Intmentioning
confidence: 99%
“…Recent studies have demonstrated that high-frequency ultrasonication (Moriwaki et al, 2005;Vecitis et al, 2008;Panchangam et al, 2009a), microwave-induced persulfate (Lee et al, 2009(Lee et al, , 2012, electrochemical method (Guan et al, 2007;Zhuo et al, 2011), and photochemical and photocatalytic methods based on 185 nm VUV or 254 nm UV (Chen et al, 2007;Cho, 2011;Giri et al, 2011aGiri et al, , 2011bGiri et al, , 2012Li et al, 2012;PhanThi et al, 2013;Hori et al, 2004Hori et al, , 2005Dillert et al, 2007;Wang et al, 2008;Wang and Zhang, 2011;Panchangam et al, 2009b;Huang et al, 2007;Park et al, 2009) can degrade PFOA in a stepwise way. In oxidative processes, generally an electron transfers from PFOA to some excited active species, such as sulfate radical anion (SO 4 U− ) (Lee et al, 2009;Hori et al, 2005), carbonate radical anions (CO 3 U− ) (PhanThi et al, 2013), photogenerated holes (Li et al, 2012;Panchangam et al, 2009b) and PFOA complexes (Wang et al, 2008;Wang and Zhang, 2011), and then a perfluoroalkyl radical is formed after decarboxylation of PFOA.…”
Section: Introductionmentioning
confidence: 99%